Systematic review on the effects of exercise with and without breakfast consumption on cognitive performance in healthy adults - Shu-Shih Hsieh; Yu Tian; Chun-Yuan Cheng; Yung-Chih Chen (BMC Psychology)
Abstract Background The objective of this systematic review was to review the current evidence on the effects of acute exercise with and without morning breakfast consumption on cognitive performance. Methods This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines and is registered in the International Prospective Register of Systematic Reviews (CRD42023396125). Studies were included if they investigated effects of acute exercise with and without preceding morning breakfast on cognitive performance measured during and following exercise in healthy adults. Eligible studies from 5 electronic databases, PubMed, Scopus, MEDLINE, Web of Science, and Embase, with no limitations on years and dates of publications to retrieve maximal number of literature (literature search and screen were completed on 13 December 2024). Study quality was assessed using the Physiotherapy Evidence Database scale (PEDro). Results A total of 3018 studies were screened. Five studies, involving 70 participants (42 women, aged between 18 and 50 years) in total (sample size per study: 10–24), were eligible for inclusion in this review. The synthesised results based on 5 identified studies with healthy adults showed that there was no indication that effects of exercise on cognitive performance (e.g., processing speed, inhibitory control) are altered by breakfast skipping and/or consumption (e.g., different portion, macronutrients, and contents). The included studies had a mean PEDro score of 4.0 (scored between 3 and 5), suggesting ‘fair’ methodological quality. Conclusion The synthesised results showed that there was no indication that effects of exercise on cognitive performance (e.g., processing speed, inhibitory control) are altered by morning breakfast consumption or macronutrients and contents of breakfast in healthy adults. However, the synthesised results should be interpreted cautiously, given the limited evidence and the heterogeneity in methodology with mostly involved young and healthy adults. Further investigation regarding interactive effects of breakfast and exercise on cognition, especially in individuals with metabolic disease or medical conditions, is warranted.